2014
DOI: 10.5935/2446-4775.20140006
|View full text |Cite
|
Sign up to set email alerts
|

Biodisponibilidade de compostos fenólicos: um importante desafio para o desenvolvimento de fármacos?

Abstract: ResumoAs substâncias fenólicas constituem uma importante classe de metabólitos secundários, amplamente distribuídas no reino vegetal. Diversas atividades biológicas in vitro são atribuídas a essa classe de substâncias. Entretanto, algumas dessas substâncias não apresentam o mesmo perfil de atividade nos ensaios in vivo. Parte disso pode ser explicada pela baixa biodisponibilidade dessas substâncias. As principais razões encontradas para este fato podem ser a baixa solubilidade em meio aquoso, a fraca estabilid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, derivatives of phenolic compounds can also reach the kidney to be excreted. Large and extensively conjugated metabolites are eliminated in the bile, while small conjugated metabolites, such as monosulfate derivatives, are excreted in urine [ 13 ]. Previous studies showed that urinary concentration of some catechins of tea ranged between 0.5–6% of initial intake, while concentration of epicatechin of cocoa in urine was up to 30% of initial intake [ 29 ].…”
Section: Metabolism and Bioavailability Of Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, derivatives of phenolic compounds can also reach the kidney to be excreted. Large and extensively conjugated metabolites are eliminated in the bile, while small conjugated metabolites, such as monosulfate derivatives, are excreted in urine [ 13 ]. Previous studies showed that urinary concentration of some catechins of tea ranged between 0.5–6% of initial intake, while concentration of epicatechin of cocoa in urine was up to 30% of initial intake [ 29 ].…”
Section: Metabolism and Bioavailability Of Phenolic Compoundsmentioning
confidence: 99%
“…An example of a plant lignan is secoisolariciresinol diglucoside. When ingested, this compound is first converted into enterodiol and eventually transformed into enterolactone by microbial enzymes in the colon [ 13 ].…”
Section: Introductionmentioning
confidence: 99%